The effect of intellectual capital on market performance with bank efficiency as a mediation variable - Siti Rachmah; Bambang Subroto; Imam Subekti (Universitas Muhammadiyah Yogyakarta, Indonesia, 2023)
Research aims: The COVID-19 pandemic caused capital market conditions, especially the banking sector, to decline. Therefore, a strategy is needed to help increase the market value of banking companies so that capital market conditions for the banking sector can be stable. The plan that can be implemented is to properly improve the management of the company's intellectual capital and improve efficiency in these banking companies so that the banking industry can develop and regain its existence in the capital market. This study aims to empirically test and prove the effect of intellectual capital on market performance mediated by banking efficiency.Design/Methodology/Approach: This study used a quantitative approach with a sample of banking sector companies on the Indonesia Stock Exchange in 2017-2021. The data met the criteria of 37 companies with a total of 117 observations. The banking efficiency testing method used Data Envelopment Analysis (DEA). Furthermore, the analysis of the hypothesis testing phase utilized multiple linear regression methods.Research findings: The study revealed that intellectual capital positively affected market performance. Second, intellectual capital had a positive impact on banking efficiency. Third, banking efficiency had a positive effect on market performance. Fourth, banking efficiency could fully mediate the relationship between intellectual capital and market performance.Practical and Theoretical Contribution/Originality: This study can provide input to companies to obtain high corporate value and competitive advantage. Thus, companies must pay attention to their intellectual capital. The results of this study were empirical evidence of the resource-based view theory in the utilization of intellectual capital and provided empirical evidence regarding the effect of intellectual capital on market performance through bank efficiency as a mediating variable.Research limitation: Business efficiency measurement utilized a non-parametric approach using Data Envelopment Analysis which has the limitation that each input and output unit is identical to other units of the same type.